2023
DOI: 10.3389/fmicb.2023.1244319
|View full text |Cite
|
Sign up to set email alerts
|

Functional genetic variation in pe/ppe genes contributes to diversity in Mycobacterium tuberculosis lineages and potential interactions with the human host

Paula Josefina Gómez-González,
Anna D. Grabowska,
Leopold D. Tientcheu
et al.

Abstract: IntroductionAround 10% of the coding potential of Mycobacterium tuberculosisis constituted by two poorly understood gene families, the pe and ppe loci, thought to be involved in host-pathogen interactions. Their repetitive nature and high GC content have hindered sequence analysis, leading to exclusion from whole-genome studies. Understanding the genetic diversity of pe/ppe families is essential to facilitate their potential translation into tools for tuberculosis prevention and treatment.MethodsTo investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…3d). This observation aligns with recent research indicating that genetic variations in pe/ppe genes contribute to the diversity observed in M. tuberculosis lineages [27] . This study establishes a correlation between the extensive variability of PE/PPE proteins in the M. marinum genome and its evolution and pathogenicity.…”
Section: Discussionsupporting
confidence: 92%
“…3d). This observation aligns with recent research indicating that genetic variations in pe/ppe genes contribute to the diversity observed in M. tuberculosis lineages [27] . This study establishes a correlation between the extensive variability of PE/PPE proteins in the M. marinum genome and its evolution and pathogenicity.…”
Section: Discussionsupporting
confidence: 92%